2010
DOI: 10.4236/health.2010.25067
|View full text |Cite
|
Sign up to set email alerts
|

The effects of slight atmospheric pressure fluctuations on the occurrence of emergency transport due to suicidal injuries

Abstract: The objective of this study was to test the hypothesis that a relation exists between slight atmospheric pressure fluctuations (APF) in the far infrasound frequency range and daily number of emergency transport events due to suicidal injuries (EESU). The regression models to compare groups were used to assess the relation of EESU to the mean daily amplitude of APF (APF-A) and to the ratio of APF amplitude averaged over the daytime to the APF amplitude averaged over the nighttime (Rdn). To eliminate the confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…He He (1) Other effects arising due to scattering of γ-rays on helium atoms [15][16][17][18][19]. As is known, the reaction [22] (2) which can proceed only through the short-living Be 8 2 nucleus with the lifetime τ ≈ 10 -16 s. However, in dense helium this nucleus may capture a third helium nucleus (and process can be continued, see "alpha process").…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He He (1) Other effects arising due to scattering of γ-rays on helium atoms [15][16][17][18][19]. As is known, the reaction [22] (2) which can proceed only through the short-living Be 8 2 nucleus with the lifetime τ ≈ 10 -16 s. However, in dense helium this nucleus may capture a third helium nucleus (and process can be continued, see "alpha process").…”
Section: Resultsmentioning
confidence: 99%
“…Analogous investigations aimed to study the possibilities of nuclear reactions were performed using HHPC (Hydrogen high pressure chambers) with Pd-rods inside [13] and in the presence of hydrogen without any metallic samples in the chamber [14,16] under irradiation by 10 MeV braking γ-rays. Possible phenomenological modeling approaches for nuclear fission reactions in the liquid-drop model and for nuclear fusion are discussed in [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Sudden weather changes such as perturbation of atmospheric pressure clearly lead to violation of basic mental and physiologic functions in humans (Didyk et al 2010, Delyukov et al 1999). Schory et al 2018 presented a positive connection of all forms of violent behavior along with the more frequent admittance in psychic hospital wards during the low atmospheric pressure in the USA, while Ruuhela et al 2009, during the investigation conducted in Finland, found that the air pressure has an effect on a suicidal behavior, especially suicide attempts with more violent methods, but within male population this impact is apparent during the lower air pressure (<1005 hPa), while females were more sensitive on higher pressure (>1020 hPa).…”
Section: Discussionmentioning
confidence: 99%